The growth of physical characteristics in male and female children - Borms, J. (Journal of Sports Sciences, 1986)
Boys and girls differ in stature. Girls experience their adolescent growth spurt and peak height velocity on average about two years earlier than boys. The growth spurt of boys lasts longer and is somewhat more intensive than in girls. Subsequently, boys tend to catch up and then pass the growth period of girls. In any random sample, there is a remarkable range in body sizes in both sexes. Still tenable hypothesis: Epiphyseal growth may be stimulated by physical activity to an optimal length but excessive and prolonged pressure can retard linear growth. There is no convincing evidence to support the view that regular and natural exercise promotes an increase in body size. There have been no studies in children of effects of training on bone growth and its mineral contents although exercise does promote these factors (actually reverses demineralization) in adults. The following aspects are discussed: aerobic power anaerobic capacity strength speed flexibility coordination and skill learning early maturation